Pendidikan Politik Berbasis Sensitivitas Gender Dalam Partai Politik Di Indonesia Dan India - Vina Salviana Darvina Soedarwo; Nurul Zuriah; Gonda Yumitro; Gautam Kumar Jha (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2020)
This research is aimed to elaborate political education concerning the issues of gender sensitivity in Indonesia and India, conducted by political parties by using comparative study. The specificity of this study is the selection of selected cases and critical problems.There are three political parties in Indonesia and three political parties in India become the subjects. Those six political parties in Indonesia and India have been conducting political education with each model and further describe the process of cadre recruitment which is typical both for the cadre of men and women based on the ideology of each party. It means that both in Indonesia and in India, the political education among political party still lack gender sensitivity. The implication, political party is needed a political education model based on gender sensitivity.